Influência do fanatismo na intenção de compra de produtos hedônicos: uma análise do comportamento de consumo do torcedor paulista - Guimarães Filho, Geraldo Prado (2016)
This study aimed to evaluate what is the influence of the fanaticism in the purchase intention of hedonic products related to soccer. For that sought to understand the influence exercised by psychological connections identification and involvement and its relations with fanaticism. The method employed was exploratory and confirmatory quantitative analysis through exploratory and confirmatory factor analysis and structural equation modeling. The survey was conducted in the city of São Paulo through a structured questionnaire. The main findings were that fanaticism is a mediator between the identification and purchase intention of hedonic products which has the effect of enhancing the relationship between them in a very relevant way. It was also shown that engagement positively affects the identification and the identification positively affects fanaticism. Another proven mediator relation was that the identification mediates the relationship between engagement and fanaticism.